Cardiovascular Complications and Short-term Mortality Risk in Community-Acquired Pneumonia - Violi, Francesco; Cangemi, Roberto; Falcone, Marco; Taliani, Gloria; Pieralli, Filippo; Vannucchi, Vieri; Nozzoli, Carlo; Venditti, Mario; Chirinos, Julio A; Corrales-Medina, Vicente F (Clinical infectious diseases, 2017)
Previous reports suggest that community-acquired pneumonia (CAP) is associated with an enhanced risk of cardiovascular complications. However, a contemporary and comprehensive characterization of this association is lacking. In this multicenter study, 1182 patients hospitalized for CAP were prospectively followed for up to 30 days after their hospitalization for this infection. Study endpoints included myocardial infarction, new or worsening heart failure, atrial fibrillation, stroke, deep venous thrombosis, cardiovascular death, and total mortality. Three hundred eighty (32.2%) patients experienced intrahospital cardiovascular events (CVEs) including 281 (23.8%) with heart failure, 109 (9.2%) with atrial fibrillation, 89 (8%) with myocardial infarction, 11 (0.9%) with ischemic stroke, and 1 (0.1%) with deep venous thrombosis; 28 patients (2.4%) died for cardiovascular causes. Multivariable Cox regression analysis showed that intrahospital Pneumonia Severity Index (PSI) class (hazard ratio [HR], 2.45, P = .027; HR, 4.23, P < .001; HR, 5.96, P < .001, for classes III, IV, and V vs II, respectively), age (HR, 1.02, P = .001), and preexisting heart failure (HR, 1.85, P < .001) independently predicted CVEs. One hundred three (8.7%) patients died by day 30 postadmission. Thirty-day mortality was significantly higher in patients who developed CVEs compared with those who did not (17.6% vs 4.5%, P < .001). Multivariable Cox regression analysis showed that intrahospital CVEs (HR, 5.49, P < .001) independently predicted 30-day mortality (after adjustment for age, PSI score, and preexisting comorbid conditions). CVEs, mainly those confined to the heart, complicate the course of almost one-third of patients hospitalized for CAP. More importantly, the occurrence of CVEs is associated with a 5-fold increase in CAP-associated 30-day mortality.